EDUCATIONAL AND PSYCHOLOGICAL COUNSELING AND ITS ROLE IN ACHIEVING THE AIMS OF THE EDUCATIONAL PROCESS – AN ANALYTICAL STUDY - Mohammad Omar AL-Momani (Jurnal Penelitian Humaniora, 2022)
Educational and psychological counseling in universities represents one of the most important means to help the student adapt the university atmosphere and get the highest degrees of success. It also helps check up the students' problems by presenting advice and guidance to them. It tries to make the student being the center of the educational process excellent in his personality in the psychological, social, academic, cultural, religious, intellectual, and sanitarian aspects. Further, it helps the student to gradually transfer from the environment of the general education to the environment of the university stage in which the student depends on himself to take decisions, identify his specialization, and improve his academic and behavioral conduct.